Terrorist financing : report of an independent task force - Greenberg, Maurice R.; Wechsler, William F.; Wolosky, Lee S. (Council on Foreign Relations, 2002)
The Independent Task Force on Terrorist Financing finds that although al-Qaeda's financial network has been disrupted, it has not been destroyed and therefore continues to threaten U.S. security. The Task Force recommends that the president designate a Special Assistant to the President for Combating Terrorist Financing, and that the United States lead international efforts to establish an organization dedicated to investigating terrorist financing.